A kind of coal gangue backfill functional material and preparation method thereof
By adding modified polyacrylamide to the functional materials of coal gangue backfill, the problems of spontaneous combustion and rekindence of coal gangue are solved, efficient flame retardant and good water retention properties of the materials are achieved, and land reclamation and ecological environment restoration are promoted.
Patent Information
- Application Number
- CN202410785465.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-06-18
AI Technical Summary
The existing technology is difficult to effectively prevent the spontaneous combustion and rekindling of coal gangue, resulting in waste of resources and ecological environment pollution. The existing governance methods are poor in effect, which is prone to secondary geological disasters.
A functional material for backfill of coal gangue is adopted, and its composition includes silt, cement, fly ash and modified polyacrylamide. By adding modified polyacrylamide, the flame retardancy and water retention properties of the material are improved, and the coal gangue is prevented from being damaged. Spontaneous combustion and rekind.
It realizes effective flame retardant of coal gangue, prevents spontaneous combustion and rekindling, improves the compressive strength and water retention properties of the materials, promotes land reclamation and ecological environment restoration, and reduces resource waste and environmental pollution.
Smart Images

Figure CN118754517B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling of coal gangue, and in particular, relates to a coal gangue backfill functional material and a preparation method thereof. Background Art
[0002] Temporary stacking or failure to fully utilize coal gangue has caused a waste of resources and triggered a series of ecological and environmental problems. Spontaneous combustion produces fly ash, acidification and other phenomena, releasing a large amount of toxic and harmful gases, PM2.5 particles, etc., polluting the air, soil and water, and is a potential ecological and environmental safety hazard. What is more serious is that the internal stacking structure of the existing gangue mountain changes after spontaneous combustion, which will cause secondary geological disasters such as mountain collapse and mudslides, endangering human living environment and life and health. A large number of studies on the spontaneous combustion mechanism of coal gangue have shown that the main factors affecting the spontaneous combustion of coal gangue are combustibles, combustion-supporting materials and temperature. However, the traditional treatment methods for spontaneous combustion of coal gangue are too simple, with poor results, and are prone to re-ignition after treatment.
[0003] At present, the capacity, scale and technology of harmless disposal and utilization of gangue cannot meet the requirements of ecological and environmental protection under the current new situation. It is now expressly prohibited to build permanent gangue dumps, and the treatment methods of ground emissions are restricted at the legal level. The "Guiding Opinions on the Comprehensive Utilization of Bulk Solid Waste" clearly pointed out that the utilization efficiency of bulk solid waste resources should be improved and the comprehensive utilization model of bulk solid waste should be innovated. In the coal industry, "gangue underground filling + ground backfilling" is promoted to promote gangue reduction. Coal enterprises are gradually turning to related technologies such as underground filling and ground backfilling. The lack of technology and application of gangue backfilling in ground mining subsidence areas, open pits and natural pits has limited the current governance means and governance capabilities. Therefore, it is necessary to conduct in-depth and systematic research based on the actual needs of backfilling and the needs of spontaneous combustion prevention and control.
[0004] At present, coal mining subsidence areas and open pits caused by coal mining activities have become a sword hanging over the heads of enterprises' environmental protection development issues. Adhering to the problem-oriented approach, understanding the mechanism of spontaneous combustion from the source, improving the existing technology for preventing spontaneous combustion of coal gangue, and increasing the resource utilization rate of coal gangue in filling coal mining subsidence areas and open pits are urgent needs of my country's coal mining areas. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a gangue backfill functional material and a preparation method thereof. The gangue backfill functional material provided by the present invention has excellent flame retardancy, and can prevent spontaneous combustion and re-ignition of gangue when used in the backfill treatment of gangue, which is conducive to land reclamation through the ground backfill of gangue, which can not only alleviate the shortage of land resources, but also repair the ecological environment, reduce the land occupation of gangue accumulation and secondary pollution to the environment, and is conducive to the localization, scale, reduction and ecological utilization of gangue.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0007] One aspect of the present invention provides a coal gangue backfill functional material, which comprises 800-1200 parts of silt, 50-60 parts of cement, 40-50 parts of fly ash and 1-5 parts of modified polyacrylamide in parts by weight;
[0008] The modified polyacrylamide is sodium bentonite modified polyacrylamide.
[0009] Another aspect of the present invention provides a method for preparing a coal gangue backfill functional material, the preparation method comprising the following steps:
[0010] (1) Preparation of sodium bentonite modified polyacrylamide:
[0011] (i) adding purified sodium bentonite to water, heating and stirring in a water bath, and then ultrasonicating and standing to obtain a sodium bentonite slurry;
[0012] (ii) adding a surfactant to the obtained sodium bentonite slurry, heating in a water bath and stirring to react, thereby obtaining an organically modified sodium bentonite;
[0013] (iii) organically modified sodium bentonite, the monomer acrylamide solution and the polyacrylamide solution are mixed evenly and vigorously stirred, then an initiator is added to carry out heating and stirring in a water bath for reaction, after the reaction is completed, ultrasonication is performed, static aging is performed, and the obtained product is dried to obtain sodium bentonite modified polyacrylamide;
[0014] (2) mixing silt, cement and fly ash according to a proportion to obtain a mixture I;
[0015] Mixing sodium bentonite-modified polyacrylamide and water uniformly to obtain a mixture II;
[0016] Mixture I and mixture II are mixed and stirred evenly, and then subjected to injection molding, curing and demoulding in sequence to obtain a finished product.
[0017] In a preferred embodiment of the present invention, in step (i), the preparation steps of the purified sodium bentonite are:
[0018] The sodium bentonite is placed in water and stirred continuously for 24 to 48 hours, then allowed to stand for aging for 20 to 28 hours, after which the upper 4 / 5 to 3 / 5 layers of slurry are taken, dried at 50 to 70°C, ground, and sieved through a 100 to 300 mesh sieve to obtain purified sodium bentonite.
[0019] In a preferred embodiment of the present invention, in step (i), the purified sodium bentonite and water are added in an amount of 1 g:20-30 mL by mass volume ratio.
[0020] In a preferred embodiment of the present invention, in step (i), the water bath heating and stirring conditions are: temperature 70-90°C, time 1-3h; the ultrasonic time is 20-40min; the standing time is 10-14h.
[0021] In a preferred embodiment of the present invention, in step (ii), the surfactant is a quaternary ammonium salt surfactant, selected from any one of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride.
[0022] In a preferred embodiment of the present invention, the surfactant is added in an amount of 1 g:600-800 mL of the sodium bentonite slurry by mass volume ratio.
[0023] In a preferred embodiment of the present invention, in step (ii), the water bath heating and stirring reaction conditions are: 60-80° C., time 1-3 h.
[0024] In a preferred embodiment of the present invention, in step (iii), the organic modified sodium bentonite, monomer acrylamide and polyacrylamide are added in an amount of 20-40 mL: 1-3 g: 1 g by volume mass ratio.
[0025] In a preferred embodiment of the present invention, the strong stirring time is 1 to 3 hours.
[0026] In a preferred embodiment of the present invention, in step (iii), the initiator is selected from any one of potassium persulfate, ammonium persulfate and sodium persulfate.
[0027] In a preferred embodiment of the present invention, the added amount of the initiator is 0.3 to 0.5 times the mass of the polyacrylamide.
[0028] In a preferred embodiment of the present invention, in step (iii), the water bath heating and stirring reaction conditions are: temperature 60-80° C., time 3-5 h.
[0029] In a preferred embodiment of the present invention, the ultrasonic time is: 20~40min.
[0030] In a preferred embodiment of the present invention, the static aging time is 20 to 28 hours.
[0031] In a preferred embodiment of the present invention, the gangue backfill functional material further comprises 1 to 3 parts of a modified polyvinyl pyrrolidone-coated boron oxide complex.
[0032] In a preferred embodiment of the present invention, the preparation method comprises the following steps:
[0033] Dissolving ammonium pentaborate and boric acid in a 20-40 wt% organic acid aqueous solution and stirring evenly to obtain a boron-containing mixed solution;
[0034] Add β-cyclodextrin to the obtained boron-containing mixed solution and stir well. Then add the cationic monomer and polyvinyl pyrrolidone, heat in a water bath at 60-80°C and stir for 1-3 hours. Then add the initiator and continue stirring for 2-6 hours. Then cool to room temperature and dry the obtained product to obtain a modified polyvinyl pyrrolidone-coated boron oxide complex.
[0035] In a preferred embodiment of the present invention, the ammonium pentaborate, boric acid and organic acid aqueous solution are added in an amount of 1 g:1-3 g:100 mL in a mass volume ratio.
[0036] In a preferred embodiment of the present invention, the organic acid is selected from any one of citric acid, acetic acid, oxalic acid and malic acid.
[0037] In a preferred embodiment of the present invention, the β-cyclodextrin, cationic monomer and polyvinyl pyrrolidone are added in a mass ratio of 1:1-3:5-10.
[0038] In a preferred embodiment of the present invention, the cationic monomer is selected from any one of methacryloyloxyethyltrimethylammonium chloride, methacryloyloxyethyldimethylbenzylammonium chloride and dimethyldiallylammonium chloride.
[0039] In a preferred embodiment of the present invention, the initiator is selected from any one of sodium persulfate, potassium persulfate and ammonium persulfate.
[0040] In a preferred embodiment of the present invention, the added amount of the initiator is 0.05 to 0.1 times the mass of polyvinyl pyrrolidone.
[0041] By means of the above technical solution, the present invention has at least the following advantages:
[0042] 1. The present invention determines the optimal ratio of silt, cement, fly ash and polyacrylamide as backfill functional materials through D-optional mixing design experiments, thereby determining the composition and content of the backfill functional material of the present invention. The backfill functional material obtained under the conditions of the composition and content has the best compressive strength and the lowest water loss rate.
[0043] 2. Sodium bentonite-modified polyacrylamide is used for the first time in the backfill functional material of the present invention. The material is a sodium bentonite-modified polyacrylamide obtained by free radical polymerization reaction of organic modified sodium bentonite as a carrier and acrylamide as a monomer under the action of an initiator. By adding sodium bentonite-modified polyacrylamide to the backfill functional material, the mechanical properties, water retention properties and thermal stability of the backfill functional material are significantly enhanced.
[0044] 3. In addition, in terms of practical application, by compounding the backfill functional material of the present invention with coal gangue to obtain backfill coal gangue and affecting the change of its thermal behavior, it is found through experiments that the coal gangue treated with the backfill functional material has good flame retardancy, which can meet the performance standards of coal gangue backfill application and realize the need to inhibit the oxidation and spontaneous combustion of coal gangue.
[0045] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a physical picture of the coal gangue backfill functional material in Example 1 of the present invention;
[0047] Figure 2 This is a site map of the coal gangue used in the present invention. DETAILED DESCRIPTION
[0048] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0050] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0051] Embodiment 1:
[0052] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 36 hours, then allowed to stand for 24 hours, and then the upper 4 / 5 layers of slurry were dried at 60°C, ground, and sieved through a 200-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:25mL, heated and stirred in a water bath at 80°C for 2 hours, then ultrasonicated for 30 minutes, and then allowed to stand for 12 hours to obtain sodium bentonite slurry. Hexadecyltrimethylammonium bromide (added at a mass volume ratio of 1g:700mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a water bath at 70°C for 2 hours to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 30 mL: 2 g: 1 g) and stirred vigorously for 2 hours. Potassium persulfate (the amount added was 0.4 times the mass of polyacrylamide) was then added and heated and stirred in a 70°C water bath for 4 hours. After the reaction was completed, ultrasonic treatment was performed for 30 minutes, and then the product was allowed to stand and age for 24 hours. The obtained product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite modified polyacrylamide.
[0053] (2) Mix 1000 parts of silt, 55 parts of cement and 45 parts of fly ash according to the proportion to obtain Mixture I. Mix 3 parts of sodium bentonite-modified polyacrylamide with 660 parts of water to obtain Mixture II. Mix Mixture I and Mixture II are mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain the finished product. Figure 1 shown.
[0054] Embodiment 2:
[0055] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 24 hours, then allowed to stand for 28 hours, and then the upper 3 / 5 layer of slurry was dried at 70°C, ground, and sieved through a 100-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:30mL, heated and stirred in a 70°C water bath for 3 hours, then ultrasonicated for 20 minutes, and then allowed to stand for 14 hours to obtain sodium bentonite slurry. Dodecyltrimethylammonium bromide (added at a mass volume ratio of 1g:600mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a 80°C water bath for 1 hour to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed evenly (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 40 mL: 1 g: 1 g) and vigorously stirred for 1 hour. Then, ammonium persulfate (the amount added was 0.5 times the mass of polyacrylamide) was added and heated and stirred in a 60°C water bath for 5 hours. After the reaction was completed, ultrasonic treatment was performed for 20 minutes, and then the product was allowed to stand and age for 28 hours. The obtained product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite modified polyacrylamide.
[0056] (2) 1200 parts of silt, 60 parts of cement and 50 parts of fly ash were mixed according to the proportion to obtain mixture I. 5 parts of sodium bentonite-modified polyacrylamide were mixed with 800 parts of water to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain a finished product.
[0057] Embodiment 3:
[0058] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 48 hours, then allowed to stand for aging for 20 hours, and then the upper 4 / 5 layers of slurry were dried at 50°C, ground, and sieved through a 300-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:20mL, heated and stirred in a 90°C water bath for 1 hour, then ultrasonicated for 40 minutes, and then allowed to stand for 10 hours to obtain sodium bentonite slurry. Tetradecyltrimethylammonium bromide (added at a mass volume ratio of 1g:800mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a 60°C water bath for 3 hours to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 20 mL: 3 g: 1 g) and stirred vigorously for 3 hours. Then, sodium persulfate (the amount added was 0.3 times the mass of polyacrylamide) was added and heated and stirred in a water bath at 80°C for 3 hours. After the reaction was completed, ultrasonic treatment was performed for 40 minutes, and then the mixture was allowed to stand for aging for 20 hours. The resulting product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite-modified polyacrylamide.
[0059] (2) 800 parts of silt, 50 parts of cement and 40 parts of fly ash were mixed according to the proportion to obtain mixture I. 1 part of sodium bentonite-modified polyacrylamide was mixed with 550 parts of water to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain a finished product.
[0060] Embodiment 4:
[0061] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 36 hours, then allowed to stand for 24 hours, and then the upper 4 / 5 layers of slurry were dried at 60°C, ground, and sieved through a 200-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:25mL, heated and stirred in a water bath at 80°C for 2 hours, then ultrasonicated for 30 minutes, and then allowed to stand for 12 hours to obtain sodium bentonite slurry. Hexadecyltrimethylammonium bromide (added at a mass volume ratio of 1g:700mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a water bath at 70°C for 2 hours to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 30 mL: 2 g: 1 g) and stirred vigorously for 2 hours. Potassium persulfate (the amount added was 0.4 times the mass of polyacrylamide) was then added and heated and stirred in a 70°C water bath for 4 hours. After the reaction was completed, ultrasonic treatment was performed for 30 minutes, and then the product was allowed to stand and age for 24 hours. The obtained product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite modified polyacrylamide.
[0062] (2) Dissolve ammonium pentaborate and boric acid in a 30 wt% citric acid aqueous solution according to the mass volume ratio of ammonium pentaborate, boric acid and citric acid aqueous solution of 1g:2g:100mL and stir evenly to obtain a boron-containing mixed solution. Add β-cyclodextrin to the obtained boron-containing mixed solution and stir evenly, then add dimethyldiallyl ammonium chloride and polyvinyl pyrrolidone, heat and stir in a water bath at 70°C for 2h, then add potassium persulfate (the amount added is 0.075 times the mass of polyvinyl pyrrolidone) and continue stirring for 4h, then cool to room temperature and dry the obtained product to obtain a modified polyvinyl pyrrolidone-coated boron oxide complex; in the above process, β-cyclodextrin, dimethyldiallyl ammonium chloride and polyvinyl pyrrolidone are added in a mass ratio of 1:2:7.5.
[0063] (3) 1000 parts of silt, 55 parts of cement and 45 parts of fly ash were mixed according to the proportion to obtain mixture I. 3 parts of sodium bentonite-modified polyacrylamide, 2 parts of modified polyvinyl pyrrolidone-coated boric oxide composite and 660 parts of water were mixed to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain a finished product.
[0064] Embodiment 5:
[0065] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 24 hours, then allowed to stand for 28 hours, and then the upper 3 / 5 layer of slurry was dried at 70°C, ground, and sieved through a 100-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:30mL, heated and stirred in a 70°C water bath for 3 hours, then ultrasonicated for 20 minutes, and then allowed to stand for 14 hours to obtain sodium bentonite slurry. Dodecyltrimethylammonium bromide (added at a mass volume ratio of 1g:600mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a 80°C water bath for 1 hour to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed evenly (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 40 mL: 1 g: 1 g) and vigorously stirred for 1 hour. Then, ammonium persulfate (the amount added was 0.5 times the mass of polyacrylamide) was added and heated and stirred in a 60°C water bath for 5 hours. After the reaction was completed, ultrasonic treatment was performed for 20 minutes, and then the product was allowed to stand and age for 28 hours. The obtained product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite modified polyacrylamide.
[0066] (2) Dissolve ammonium pentaborate and boric acid in a 40 wt% citric acid aqueous solution according to the mass volume ratio of ammonium pentaborate, boric acid and citric acid aqueous solution of 1g:3g:100mL and stir evenly to obtain a boron-containing mixed solution. Add β-cyclodextrin to the obtained boron-containing mixed solution and stir evenly, then add methacryloyloxyethyl trimethyl ammonium chloride and polyvinyl pyrrolidone, heat and stir in a water bath at 60°C for 3h, then add ammonium persulfate (the amount added is 0.1 times the mass of polyvinyl pyrrolidone) and continue stirring for 6h, then cool to room temperature and dry the obtained product to obtain a modified polyvinyl pyrrolidone-coated boron oxide complex; in the above process, β-cyclodextrin, methacryloyloxyethyl trimethyl ammonium chloride and polyvinyl pyrrolidone are added in a mass ratio of 1:3:10.
[0067] (3) 1200 parts of silt, 60 parts of cement and 50 parts of fly ash were mixed according to the proportion to obtain mixture I. 5 parts of sodium bentonite-modified polyacrylamide, 3 parts of modified polyvinyl pyrrolidone-coated boric oxide composite and 800 parts of water were mixed to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain the finished product.
[0068] Embodiment 6:
[0069] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 48 hours, then allowed to stand for aging for 20 hours, and then the upper 4 / 5 layers of slurry were dried at 50°C, ground, and sieved through a 300-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:20mL, heated and stirred in a 90°C water bath for 1 hour, then ultrasonicated for 40 minutes, and then allowed to stand for 10 hours to obtain sodium bentonite slurry. Tetradecyltrimethylammonium bromide (added at a mass volume ratio of 1g:800mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a 60°C water bath for 3 hours to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 20 mL: 3 g: 1 g) and stirred vigorously for 3 hours. Then, sodium persulfate (the amount added was 0.3 times the mass of polyacrylamide) was added and heated and stirred in a water bath at 80°C for 3 hours. After the reaction was completed, ultrasonic treatment was performed for 40 minutes, and then the mixture was allowed to stand for aging for 20 hours. The resulting product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite-modified polyacrylamide.
[0070] (2) Dissolve ammonium pentaborate and boric acid in a 20 wt% citric acid aqueous solution in a mass volume ratio of 1 g:1 g:100 mL, and stir evenly to obtain a boron-containing mixed solution. Add β-cyclodextrin to the obtained boron-containing mixed solution and stir evenly, then add methacryloyloxyethyl dimethyl benzyl ammonium chloride and polyvinyl pyrrolidone, heat and stir in a water bath at 80°C for 1 hour, then add sodium persulfate (the amount added is 0.05 times the mass of polyvinyl pyrrolidone) and continue stirring for 2 hours, then cool to room temperature and dry the obtained product to obtain a modified polyvinyl pyrrolidone-coated boron oxide complex; in the above process, β-cyclodextrin, methacryloyloxyethyl dimethyl benzyl ammonium chloride and polyvinyl pyrrolidone are added in a mass ratio of 1:1:5.
[0071] (3) 800 parts of silt, 50 parts of cement and 40 parts of fly ash were mixed according to the proportion to obtain mixture I. 1 part of sodium bentonite-modified polyacrylamide, 1 part of modified polyvinyl pyrrolidone-coated boric oxide composite and 550 parts of water were mixed to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain a finished product.
[0072] Comparative Example 1:
[0073] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 36 hours, then allowed to stand for 24 hours, and then the upper 4 / 5 layers of slurry were dried at 60°C, ground, and sieved through a 200-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite was added to water at a mass volume ratio of 1g:25mL, heated and stirred in a water bath at 80°C for 2 hours, then ultrasonicated for 30 minutes, and then allowed to stand for 12 hours to obtain sodium bentonite slurry. Hexadecyltrimethylammonium bromide (added at a mass volume ratio of 1g:700mL to the sodium bentonite slurry) was added to the obtained sodium bentonite slurry and heated and stirred in a water bath at 70°C for 2 hours to obtain organically modified sodium bentonite. The organically modified sodium bentonite, monomer acrylamide solution and polyacrylamide solution were mixed (the organically modified sodium bentonite, monomer acrylamide and polyacrylamide were added in a volume mass ratio of 30 mL: 2 g: 1 g) and stirred vigorously for 2 hours. Potassium persulfate (the amount added was 0.4 times the mass of polyacrylamide) was then added and heated and stirred in a 70°C water bath for 4 hours. After the reaction was completed, ultrasonic treatment was performed for 30 minutes, and then the product was allowed to stand and age for 24 hours. The obtained product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite modified polyacrylamide.
[0074] (2) β-cyclodextrin was added to a 30 wt % citric acid aqueous solution and stirred thoroughly. Then, dimethyldiallyl ammonium chloride and polyvinyl pyrrolidone were added and heated in a water bath at 70° C. and stirred for 2 h. Potassium persulfate (the amount added was 0.075 times the mass of polyvinyl pyrrolidone) was added and stirred for 4 h. The mixture was then cooled to room temperature and the resulting product was dried to obtain modified polyvinyl pyrrolidone. In the above process, β-cyclodextrin, dimethyldiallyl ammonium chloride and polyvinyl pyrrolidone were added in a mass ratio of 1:2:7.5.
[0075] (3) 1000 parts of silt, 55 parts of cement and 45 parts of fly ash were mixed according to the proportion to obtain mixture I. 3 parts of sodium bentonite-modified polyacrylamide, 2 parts of modified polyvinyl pyrrolidone and 660 parts of water were mixed to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain the finished product.
[0076] Comparative Example 2:
[0077] (1) Preparation of sodium bentonite modified polyacrylamide: Sodium bentonite was placed in water and stirred continuously for 36 hours, then allowed to stand for 24 hours, and then the upper 4 / 5 layers of slurry were dried at 60°C, ground, and sieved through a 200-mesh sieve to obtain purified sodium bentonite. Purified sodium bentonite, monomer acrylamide solution, and polyacrylamide solution were mixed (purified sodium bentonite, monomer acrylamide, and polyacrylamide were added in a volume mass ratio of 30 mL: 2 g: 1 g) and stirred vigorously for 2 hours, and then potassium persulfate (the amount added was 0.4 times the mass of polyacrylamide) was added and heated and stirred in a 70°C water bath for 4 hours. After the reaction was completed, ultrasonic treatment was performed for 30 minutes, and then allowed to stand for 24 hours. The resulting product was placed in a constant temperature drying oven and dried at 60°C to obtain sodium bentonite modified polyacrylamide.
[0078] (2) 1000 parts of silt, 55 parts of cement and 45 parts of fly ash were mixed according to the proportion to obtain mixture I. 3 parts of sodium bentonite-modified polyacrylamide were mixed with 660 parts of water to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain a finished product.
[0079] Comparative Example 3:
[0080] (1) Preparation of modified polyacrylamide: monomer acrylamide solution and polyacrylamide solution were mixed (monomer acrylamide and polyacrylamide were added in a volume mass ratio of 30 mL: 2 g: 1 g) and stirred vigorously for 2 h. Potassium persulfate was then added (the amount added was 0.4 times the mass of polyacrylamide) and heated in a 70 °C water bath with stirring for 4 h. After the reaction was completed, ultrasonication was performed for 30 min, and then the product was allowed to stand for 24 h. The resulting product was placed in a constant temperature drying oven and dried at 60 °C to obtain modified polyacrylamide.
[0081] (2) 1000 parts of silt, 55 parts of cement and 45 parts of fly ash were mixed according to the proportion to obtain mixture I. 3 parts of modified polyacrylamide and 660 parts of water were mixed evenly to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then subjected to injection molding, curing and demolding in sequence to obtain a finished product.
[0082] Comparative Example 4:
[0083] 1000 parts of silt, 55 parts of cement and 45 parts of fly ash were mixed according to the proportion to obtain mixture I. 3 parts of polyacrylamide and 660 parts of water were mixed evenly to obtain mixture II. Mixture I and mixture II were mixed and stirred evenly, and then injection molding, curing and demoulding were carried out in sequence to obtain a finished product.
[0084] Comparative Example 5:
[0085] 1000 parts of silt, 55 parts of cement and 45 parts of fly ash were mixed according to a proportion to obtain a mixture I. The mixture I was mixed with 660 parts of water and stirred evenly, and then subjected to injection molding, curing and demoulding in sequence to obtain a finished product.
[0086] Test Example 1: Compressive Strength Test of Different Gangue Backfill Functional Materials
[0087] The compressive strength of the samples of coal gangue backfill functional materials in Examples 1 to 6 and Comparative Examples 1 to 5 was tested in accordance with GB / T17671-1999 "Test Method for Cement Mortar Strength (ISO Method)". In this test, the axial strain rate was 1 mm / min, and the sample was prepared by 100 mm*50 mm cylindrical test mold. After demolding, the sample was placed in a constant temperature (25 ℃ ± 2 ℃) and constant humidity (95% ± 3%) curing box for curing, and the compressive strength at 7 d, 14 d, 28 d, and 60 d was measured. Three parallel test blocks were set for each group, and the test results were taken as the average compressive strength, accurate to 0.01 kPa. The test values that were too large or too small were removed.
[0088] Compressive strength calculation formula:
[0089] P c =F c / A
[0090] Where: P c —compressive strength, MPa;
[0091] F c —The maximum load when the sample is destroyed, N;
[0092] A—Stress area of sample mm 2 .
[0093] The test results of compressive strength are shown in Table 1.
[0094] Table 1 Compressive strength test results of different backfill functional materials
[0095]
[0096] The results in Table 1 show that the compressive strength of the backfill functional materials of Examples 1 to 6 and Comparative Examples 1 to 5 at 7 d, 14 d, 28 d, and 60 d increases with the increase in the number of curing days. Although the compressive strength of the backfill functional materials of Comparative Examples 1 to 5 becomes stronger with the increase in the number of curing days, there is still a significant gap between the compressive strength of the backfill functional materials of Examples 1 to 6. In the backfill functional materials of Examples 1 to 3, the sodium bentonite-modified polyacrylamide enhances the adsorption of the anionic modified polyacrylamide on the clay by means of physical crosslinking or slight chemical crosslinking between the sodium bentonite and the modified polyacrylamide polymer molecules, improves the bonding effect of the clay particles in the backfill functional materials, and improves the compressive strength of the sodium bentonite-modified polyacrylamide. In the backfill functional materials of Examples 4 to 6, the compressive strength of the backfill functional materials can be further improved by adding a modified polyvinyl pyrrolidone-coated boron oxide complex.
[0097] Test Example 2: Water loss rate detection of different coal gangue backfill functional materials
[0098] The water retention capacity of materials is a reflection of the water retention performance and effect of materials after temperature changes. Materials can absorb a large amount of water during the preparation process. When the external temperature changes, dehydration and reabsorption of water occur. Water loss rate is an important parameter for examining the water retention capacity of materials. The water loss rate is used as an indicator to analyze the changing trend of temperature sensitivity before and after material modification. By statistically analyzing the water loss rate of backfill functional materials and analyzing the relationship curve between the water loss rate of backfill functional materials and time and temperature, the water retention stability effect of materials is evaluated.
[0099] The water loss rate determination method of the gangue backfill functional material samples in Examples 1 to 6 and Comparative Examples 1 to 5 adopts the constant temperature weighing method. The soil temperature in the backfill area generally does not exceed 40°C, so the temperature selected for the constant temperature heating experiment is 40°C. The sample preparation is formed and maintained at a constant temperature and humidity for 28 days until it is stable. The sample to be tested is taken out and placed in a 40°C constant temperature drying oven. The water loss rate data of the sample is observed and recorded every 2 hours from 0 to 14 h at 40°C. The temperature heating experiment selects a range of 20°C to 140°C. The water loss rate of the sample is calculated as follows:
[0100]
[0101] Where ω refers to water loss rate, %;
[0102] m1 is the mass of the initial sample, g;
[0103] m2 is the mass of the sample after weight loss, g.
[0104] The test results of water loss rate are shown in Table 2.
[0105] Table 2 Water loss test results of different gangue backfill functional materials
[0106]
[0107] As can be seen from Table 2, in the 40°C constant temperature heating experiment, the water loss rate of the samples of Examples 1 to 6 and Comparative Examples 1 to 5 increases with time, and can maintain a steady upward trend. The backfill functional materials of Examples 1 to 5 have a significantly lower water loss rate than the backfill functional materials of Comparative Examples 1 to 5, which indicates that the addition of sodium bentonite modified polyacrylamide significantly improves the water retention performance of the backfill functional materials. The backfill functional materials of Examples 4 to 6 have a lower water loss rate than the backfill functional materials of Examples 1 to 3, which indicates that the water retention performance of the backfill functional materials is significantly improved by adding the modified polyvinyl pyrrolidone-coated boron oxide composite.
[0108] Test Example 3: Application of backfill functional materials in coal gangue treatment
[0109] The experiment used coal gangue from the waste dump of Bulianta Coal Mine in Shendong Mining Area, such as Figure 2 As shown. The gangue was crushed into particles less than 6 mm, sieved according to different particle size gradients, and appropriate amount of gangue samples were taken for testing of physical and chemical properties. The microscopic appearance of the gangue observed by scanning electron microscopy (SEM) showed that many layered and flaky structures appeared in the sample, and the surface of the block particles also had linear flaky structures and the pores were relatively developed.
[0110] First, the backfill functional materials of Examples 1, 4 and Comparative Examples 1 to 5 were mixed with coal gangue in an amount of 30% to prepare the corresponding experimental samples, and finally prepared into samples 1 to 7 with a specification of 100 mm*100 mm*10 mm, and maintained at a constant temperature and humidity for 28 days to make the samples reach a stable state. During the experiment, the backfill functional materials mixed with coal gangue samples 1 to 7 were wrapped with thermal insulation cotton, placed on a 70 ℃ constant temperature electric heating plate, and the time of continuous constant temperature for 2 hours was recorded as the effective heat resistance time. The surface temperature of the sample was monitored and recorded in real time using an infrared camera, and then the influence of different backfill functional material thicknesses on its thermal stability was evaluated. According to this experiment, the heating conditions of the backfill functional materials in the low-temperature oxidation stage of coal gangue were simulated to analyze its thermal stability and heat resistance. The surface temperature of different backfill functional materials was statistically changed over time, and the results are shown in Table 3.
[0111] Table 3 Changes of surface temperature of coal gangue samples mixed with different backfill functional materials over time
[0112] Temperature (℃) Temperature (℃) Temperature (℃) Temperature (℃) Temperature (℃) Temperature (℃) Temperature (℃) Temperature (℃) Temperature (℃) Sample No. 0min 15min 30min 45min 60min 75 min 90 min 105min 120min 1 21.5 26.9 31.7 33.7 35.2 35.8 36.3 36.8 37 2 21.4 24.6 29.1 31.5 32.9 33.8 34 34.4 34.4 3 21.5 30.5 35.1 37.1 38.4 38.6 38.8 39.2 40 4 21.4 31.4 36.7 39.3 40.5 41.6 42.1 42.8 43.6 5 21.5 29.5 42.4 44.7 47.9 49.2 52.1 53.3 54.5 6 21.6 44.2 45.3 48.1 50.3 52.9 54.4 55.1 56.2 7 21.6 46.3 47.8 49.9 52.2 53.9 55.7 56.8 57.9
[0113] It can be seen from the results in Table 3 that with the extension of time, the surface temperature of the samples of coal gangue mixed with backfill functional materials of different numbers tends to increase, but compared with the surface temperature change trend of samples No. 3 to 7, the surface temperature increase rate of samples No. 1 to 2 is significantly lower, and finally at 120 minutes, the surface of samples No. 1 to 2 has a lower temperature, which shows that the coal gangue added with the backfill functional materials of Examples 1 and 4 of the present invention can achieve the purpose of physical shielding, isolating heat sources, and inhibiting the combination of coal and oxygen, enhance the overall stability of the material, improve the overall thermal conductivity, inhibit the temperature rise of coal gangue, and thus reduce the natural tendency of coal gangue.
[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a coal gangue backfill functional material, characterized in that: The gangue backfill functional material comprises, by weight, 800 to 1200 parts of silt, 50 to 60 parts of cement, 40 to 50 parts of fly ash and 1 to 5 parts of modified polyacrylamide; The modified polyacrylamide is sodium bentonite modified polyacrylamide; The preparation method comprises the following steps: (1) Preparation of sodium bentonite modified polyacrylamide: (i) adding purified sodium bentonite to water, heating and stirring in a water bath, and then ultrasonicating and standing to obtain a sodium bentonite slurry; (ii) adding a surfactant to the obtained sodium bentonite slurry, heating in a water bath and stirring to react, thereby obtaining an organically modified sodium bentonite; (iii) organically modified sodium bentonite, the monomer acrylamide solution and the polyacrylamide solution are mixed evenly and vigorously stirred, then an initiator is added to carry out heating and stirring in a water bath for reaction, after the reaction is completed, ultrasonication is performed, and the product is allowed to stand for aging, and the obtained product is dried to obtain sodium bentonite modified polyacrylamide; (2) mixing silt, cement and fly ash according to a proportion to obtain a mixture I; Mixing sodium bentonite-modified polyacrylamide and water uniformly to obtain a mixture II; Mixture I and mixture II are mixed and stirred evenly, and then subjected to injection molding, curing and demoulding in sequence to obtain a finished product.
2. The method for preparing the coal gangue backfill functional material according to claim 1, characterized in that: In step (i), the preparation steps of the purified sodium bentonite are: The sodium bentonite is placed in water and stirred continuously for 24 to 48 hours, then allowed to stand for aging for 20 to 28 hours, after which the upper 4 / 5 to 3 / 5 layer of slurry is taken out and dried at 50 to 70° C., ground, and sieved through a 100 to 300 mesh sieve to obtain purified sodium bentonite.
3. The method for preparing the coal gangue backfill functional material according to claim 1, characterized in that: In step (i), the purified sodium bentonite and water are added in an amount of 1 g:20-30 mL by mass volume ratio.
4. The method for preparing the gangue backfill functional material according to claim 1, characterized in that: In step (i), the water bath heating and stirring conditions are: temperature 70-90° C., time 1-3 h; the ultrasonic time is 20-40 min; the standing time is 10-14 h.
5. The method for preparing the coal gangue backfill functional material according to claim 1, characterized in that: In step (ii), the surfactant is a quaternary ammonium salt surfactant, selected from any one of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; The surfactant is added in an amount according to a mass volume ratio of 1g:600-800mL to the sodium bentonite slurry.
6. The method for preparing the gangue backfill functional material according to claim 1, characterized in that: In step (ii), the reaction conditions of heating and stirring in a water bath are: 60-80° C., and the time is 1-3 h.
7. The method for preparing the coal gangue backfill functional material according to claim 1, characterized in that: In step (iii), the organic modified sodium bentonite, monomer acrylamide and polyacrylamide are added in an amount of 20-40 mL: 1-3 g: 1 g in a volume-to-mass ratio; The strong stirring time is 1 to 3 hours.
8. The method for preparing the gangue backfill functional material according to claim 1, characterized in that: In step (iii), the initiator is selected from any one of potassium persulfate, ammonium persulfate, and sodium persulfate; The added amount of the initiator is 0.3 to 0.5 times the mass of the polyacrylamide.
9. The method for preparing the coal gangue backfill functional material according to claim 1, characterized in that: In step (iii), the water bath heating and stirring reaction conditions are: temperature 60-80°C, time 3-5h; The ultrasonic time is: 20 to 40 minutes; The static aging time is 20 to 28 hours.
Citation Information
Patent Citations
Coal gangue-containing foundation pit backfill material and preparation method thereof
CN112521097A
Soil matrix and gangue landfill reclamation method
CN118160600A
Composite impermeable material as well as preparation method and application thereof
CN118164728A